Proses Rekrutmen dan Seleksi: Potensi Ketidakefektifan dan Faktornya - Millenia Titisari; Khairul Ikhwan (Universitas Islam Kadiri, 2021)
Ineffectiveness in the recruitment and selection process can be detrimental to the company. Companies need to minimize the inefeectiveness that occurs in the recruitment and selection process. Meanwhile, the literature that provides empirical evidence on factors of recruitment ineffectiveness and its resolution is very diverse and not comprehensive. This study aims to provide a comprehensive picture of potential ineffectiveness in the recruitment and selection process for employess in Indonesia. A systematic study of literature is used in this study. The sample was obtained from 17 national journals that have been published and have been accredited and have an ISSN during the period 2006 to 2021 regarding recruitment and selection. There are 18 articles relevant to the research. This study groups articles covering topics, research methods and research sectors. The results of this study indicate that the most widely studied research topics come from the dependent variable, namely Civil Servants and employee performance, while the research method used is mostly qualitative methods, as well as the most studied sector, namely the public sector and various forms of process ineffectiveness.